Vestibular modulation of muscle sympathetic nerve activity during sinusoidal linear acceleration in supine humans - Hammam, Elie; Bolton, Philip S.; Kwok, Kenny; Macefield, Vaughan G. (Frontiers in Neuroscience, 2014)
The utricle and saccular components of the vestibular apparatus detect linear displacements of the head in the horizontal and vertical planes, respectively. We previously showed that sinusoidal linear acceleration in the horizontal plane of seated humans causes a pronounced modulation of muscle sympathetic nerve activity (MSNA), supporting a significant role for the utricular component of the otolithic organs in the control of blood pressure. Here we tested the hypothesis that the saccule can also play a role in blood pressure regulation by modulating lower limb MSNA. Oligounitary MSNA was recorded via tungsten microelectrodes inserted into the common peroneal nerve in 12 subjects, laying supine on a motorised platform with the head aligned with the longitudinal axis of the body. Slow sinusoidal linear accelerations-decelerations (peak acceleration ±4 mG) were applied in the rostrocaudal axis (which predominantly stimulates the saccule) and in the mediolateral axis (which engages the utricle) at 0.08 Hz. The modulation of MSNA in the rostrocaudal axis (29.4 ± 3.4%) was similar to that in the mediolateral axis (32.0 ± 3.9%), and comparable to that obtained by stimulation of the utricle alone in seated subjects with the head vertical. We conclude that both the saccular and utricular components of the otolithic organs play a role in the control of arterial pressure during postural challenges.